# (-2^x + 99) [-2^(x-1)] = 48, how do you solve this?

If someone can answer in step by step that would be helpful

Update:

@mike G how did you get to that first step

### 2 Answers

Relevance

- PranilLv 78 years agoFavorite Answer
(-2^x + 99) [-2^(x-1)] = 48

(-2^x + 99) [-2^x/2^1)] = 48

(-2^x + 99) [-2^x] = 96

4^x – 99(2^x) = 96

2^2^x = 99(2^x) + 96 --------- Let 2^x = a

a^2 – 99a + 96 = 0

a = [99 ± √99² – 384]/2

a = 98.01 or 0.98

2^x = 98.01 or 2^x = 0.98

x log 2 = log 98.01

x = 1.9913/0.3010 = 6.62

or

x = – 0.02915

----

- Mike GLv 78 years ago
2^(2x-1)-99*2^(x-1)-48 = 0

2^2x-99*2^x - 96 = 0

2^x = [99±sqrt(10185)]/2

2^x = 99.96

xlog2 = log99.96

x = 6.6433

Still have questions? Get your answers by asking now.